Site-Specific Immunomodulator: A Novel Treatment for Crohn's Disease. (12th May 2015) - Bressler, Brian; Bethel, Kevin P.; Kleef, Ralf; Reynolds, Sophie L.; Sutcliffe, Simon; Mullins, David W.; Gunn, Hal
Abstract : We investigated the mechanism of action, safety, and efficacy of the Site-Specific Immunomodulator (SSI) QBECO, a novel immunotherapy for Crohn's disease (CD). Using human monocytic THP-1 cells, we demonstrate that SSI QBECO (derived from the common colon bacteria E. coli ) activates macrophages to an M1 phenotype (associated with enhanced capacity to eliminate bacteria and activate innate immune responses). We assessed SSI QBECO in a compassionate use protocol of ten adult patients with active CD. Patients with moderate to severe clinical symptoms receiving conventional CD treatments and/or complementary therapies were included, except patients receiving anti-TNF medications. SSI QBECO was self-administered subcutaneously every second day, for a minimum of 2.5 months and a maximum of 11 months. All 10 patients reported improvement of symptoms while on the SSI QBECO treatment. Seven patients reported full resolution of clinical symptoms during a course of SSI QBECO of at least three months. Three patients have experienced ongoing sustained clinical remission after discontinuing all medications, including SSI treatment. The longest case of clinical remission is still ongoing (>4 years). No serious severe adverse clinical events were reported. Collectively, we conclude that treatment with the immunoactive SSI QBECO was well tolerated and effective for treatment of Crohn's disease in this case series.